Karakteristik Orang Tua dan Status Perkembangan Anak Usia 30-72 Bulan - Rica Anjayani; Sri Rahayu; Tecky Afifah Santi Amartha (Midwifery Care Journal, 2024)
The prevalence of developmental deviations in children aged 5 years in Indonesia reported by WHO in 2016 was 7,512.6 per 100,000 population (7.51%). In PAUD Permata UNDIP there are 1.7% of children aged 30-72 months with deviant development. Development is influenced by internal and external factors. The aim of the study was determined the analysis of factors that influence the developmental status of children aged 30-72 months at PAUD Permata UNDIP. The research used a quantitative, analytic research design with a cross-sectional approach. The population of this study were all pre-school children and mothers who had children aged 30-72 months at Permata UNDIP PAUD, Semarang City, Central Java. The sampling technique used the total sampling technique so that 49 samples were obtained. Data collection used a questionnaire given to the students' mothers as well as a pre-screening developmental questionnaire (KPSP).The results show that the p value of the mother's education level is 0.000; mother's occupation 0.001; history of exclusive breastfeeding 0.001; child nutritional status 0.000; BBLR status 0.000; with ɑ = 0.01 there is a significant relationship between the above variables and the developmental status of children aged 30-72 months. From the factors that have been studied, the mother's education level and low birth weight (LBW) status are factors that have a strong relationship. The higher the level of mother's education, the better knowledge will be produced so that it can reduce deviations in child development.The community was expected to monitor child development and collaborate with health workers using the KPSP check-list sheet